2020
DOI: 10.1002/ajhb.23439
|View full text |Cite
|
Sign up to set email alerts
|

Medieval menarche: Changes in pubertal timing before and after the Black Death

Abstract: Objectives Bioarcheological evidence suggests stature increased in males but decreased in females after the Black Death (1348‐1350 CE). Because tradeoffs between growth and reproduction can result in earlier ages at menarche and lower limb length, we assess menarcheal age between 1120 and 1540 CE to better understand the health of medieval adolescent females before and after the plague. Materials and Methods Our sample comprises 74 adolescent females from St. Mary Spital, London (1120‐1540 CE) within the age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 100 publications
(137 reference statements)
1
20
0
Order By: Relevance
“…Similarly, age-at-menarche was placed between 15 and 17 years in medieval Hispano-Muslims . Changes in the timing of menarche before and after the Black Death have also been observed in a recent bioarcheological study that highlights the importance of tradeoffs between individual growth and reproduction (DeWitte & Lewis, 2021). Pubertal patterns observed in archaeological populations could be advantageous; delays in growth and development, especially in later adolescence, give individuals the chance for catch-up growth (Simondon et al, 1998).…”
Section: Puberty: From Child To Adultmentioning
confidence: 74%
“…Similarly, age-at-menarche was placed between 15 and 17 years in medieval Hispano-Muslims . Changes in the timing of menarche before and after the Black Death have also been observed in a recent bioarcheological study that highlights the importance of tradeoffs between individual growth and reproduction (DeWitte & Lewis, 2021). Pubertal patterns observed in archaeological populations could be advantageous; delays in growth and development, especially in later adolescence, give individuals the chance for catch-up growth (Simondon et al, 1998).…”
Section: Puberty: From Child To Adultmentioning
confidence: 74%
“…The gracile female US 8432 exhibited some indicators of severe physiological stress experienced during childhood, similarly to what is documented in other osteoarcheological cases of maternal death (e.g., Flores & Sánchez, 2007; Willis & Oxenham, 2013). According to DeWitte and Lewis (2020), in females experiencing early menarche, the premature attainment of sexual maturity could lead to reproduction at a younger age, possibly resulting in a shorter stature. Interestingly, a short stature (148.6 ± 3.41 cm) was indeed observed in the case of the individual US 8432 from Pieve di Pava.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses from before, during, and after the Black Death in Denmark showed that urbanization had differential impacts on survivorship across the lifespan (Kelmelis & DeWitte, 2021 ). Further, despite potential sex differences following the pandemic (e.g., DeWitte, 2018 ; DeWitte & Lewis, 2021 ), research on whether sex was associated with previous stress, frailty, and thus mortality risks during the Black Death and subsequent recurring plagues has produced mixed results (Curtis & Roosen, 2017 ; DeWitte, 2009 , 2010 ; Godde, Pasillas, & Sanchez, 2020 ).…”
Section: Anthropological Approaches To Infectious Diseasementioning
confidence: 99%